Prediction of weld toe magnification factors for semi-elliptical cracks in X-joints under bending loading - Akbar Ali, Esmah Kamarudeen (2014)
This project reports mainly the background development of the sets of equations for estimating the weld toe magnification factors (Mk)) for semi-elliptical cracks in X-joint (cruciform joint) under bending loading. The report also includes equations for those subjected to membrane (axial) loading.